Organizational Support for Nurses' Career Planning and Development : A Scoping Review - Kallio, Hanna; Liljeroos, Hanna; Koivunen, Marita; Kuusisto, Anne; Hult, Marja; Kangasniemi, Mari (Wiley-Hindawi, 2025)
Aim. To systematically map and identify key knowledge on organizational support for nurses' career planning and development. Design. Scoping review. Methods. Systematic electronic searches were carried out with the CINAHL, PubMed, Scopus, and Web of Science databases in May 2022. The searches were limited to scientific, peer-review papers that were published in English from January 2012 to May 2022. Data were extracted and synthetized and are presented in tables and text. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results. We identified 1,400 papers and 28 met the inclusion criteria. Organizations recognized nurses' career planning and development in relation to the individual's professional development and the organization's need to promote high-quality services and workforce engagement. The organizational support included strategic work to ensure there were adequate resources and purposeful vacancies and a structured framework based on objective qualification criteria and equal assessment. Organizations focused on sharing knowledge, structured career planning, and interpersonal support. Support within the nursing profession and multilayered interprofessional collaboration were also important. Conclusion. Nurses' career planning and development was linked to their personal development and the organization's aims and required support from both fellow nurses and other professionals. Implications for the Nursing Management. Identifying the organizational structures and methods that are needed to support nurses' career planning and development can help nursing management to evaluate and develop strategies that improve the attractiveness of a nursing career and nurses' engagement.